PENGARUH CARBON EMISSION DISCLOUSER TERHADAP NILAI PERUSAHAAN DENGAN ENVIRONMENTAL PERFORMANCE SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Alya Ghina Meidita; Dwi Ratmono (Diponegoro Journal of Accounting, 2026)
This study aims to obtain empirical evidence regarding the influence of carbon emission disclosure on firm value and the role of environmental performance in moderating this influence. This research also includes control variables, such as company size and leverage.This sample was selected using a purposive sampling method, focusing on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2021-2023. The data used are secondary data obtained from annual reports and sustainability reports. The analytical method used is Structural Equation Modeling-Partial Least Squares (SEM-PLS), which was tested using the SmartPLS Version 4.0.The results of this study indicate that carbon emission disclosure has a positive influence on firm value. Meanwhile, environmental performance does not moderate the influence of carbon emission disclosure on firm value, as the moderating effect is not statistically significant.